FUNERAL DIRGES OF THE AKAN PEOPLE, by J. H. Nketia. Published by Achimota, Gold Coast, 1955. Blocks and Samples of musical transcriptions 296 pp. (International Library of African Music, 1956)
pages: 82
Keywords: African Music